Evaluation of the cold tolerance of Saccharum spontaneum L. clones with different ploidy levels on the basis of morphological and physiological indices. (15th April 2020) - Yang, H.‐L.; Yu, X.‐H.; Wang, C.‐F.; Yang, Y.; Wang, X.‐H.; Yang, Q.‐H.
Abstract: Saccharum spontaneum L. is one of the most important germplasm resources for modern sugarcane breeding. Exploring the cold tolerance of S. spontaneum clones with different ploidy levels and screening for cold‐tolerant material can be helpful in parent selection for breeding cold‐tolerant sugarcane. Morphological indices, leaf ultrastructure and physiological indices were used to evaluate the cold tolerance of 36 S. spontaneum clones with different ploidy levels (2n = 40, 48, 54, 60, 64, 78, 80, 88, 92 and 96). The morphological indices of S. spontaneum clones with different ploidy levels were positively correlated with ploidy. Under low‐temperature stress, the chloroplast and mitochondrial structures of the clones with high ploidy were more severely damaged than were those of clones with low ploidy. A comprehensive evaluation of the physiological indices showed that the 36 S. spontaneum clones could be divided into four categories: strongly cold tolerant, cold tolerant, moderately cold tolerant and cold sensitive. Correlation analysis of the morphological indices and cold tolerance revealed a significant negative correlation between cold tolerance and ploidy. On the basis of the morphological and physiological indices, optimal stepwise regression equations that can be used for the selection of cold‐tolerant S. spontaneum resources were established. The S. spontaneum clones with low ploidy are more cold tolerant than those with high ploidy. Clones 12‐37, 13‐10 and 12‐23 are strongly cold‐tolerant germplasm resources, which suggests these germplasm sources have high potential for use in breeding cold‐tolerant sugarcane. Abstract : The morphological and physiological indexes of 36 S. spontaneum clones with 10 different ploidy levels showed that S. spontaneum clones with low ploidy are more cold tolerant than those with high ploidy.